2015
DOI: 10.3133/sim3336
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of marsh types from Corpus Christi Bay, Texas, to Perdido Bay, Alabama, in 2010

Abstract: Coastal zone managers and researchers often require detailed information regarding emergent marsh vegetation types (that is, fresh, intermediate, brackish, and saline) for modeling habitat capacities and needs of marsh dependent taxa (such as waterfowl and alligator).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…First, both sites needed to be representative of similar marsh types in Louisiana. The coastal zone of Louisiana has approximately 2144 km 2 of brackish marsh and approximately 2837 km 2 of freshwater marsh [ Enwright et al ., ], and both sites have vegetation assemblages and hydrological signatures consistent with these wetland types. Many brackish marshes in Louisiana dominated by Spartina patens (Aiton) Muhl.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…First, both sites needed to be representative of similar marsh types in Louisiana. The coastal zone of Louisiana has approximately 2144 km 2 of brackish marsh and approximately 2837 km 2 of freshwater marsh [ Enwright et al ., ], and both sites have vegetation assemblages and hydrological signatures consistent with these wetland types. Many brackish marshes in Louisiana dominated by Spartina patens (Aiton) Muhl.…”
Section: Methodsmentioning
confidence: 91%
“…We thank Brian Bergamaschi, Ankur Desai, and three anonymous referees for providing excellent reviews of previous manuscript drafts, as well as Brady Couvillion for extracting Louisiana‐specific marsh area estimates from Enwright et al . []. Any use of trade, product, or firm names is for descriptive purposes only and does not imply endorsement by the U.S. Government.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…To characterize habitat covariates at the scale of the study site, we used a United States Geological Survey raster file (Enwright et al ) in ArcGIS to estimate percent cover of intermediate‐brackish marsh (intermediate marsh; salinity = 3.4–8.3 ppt) and open water at each study site. We used intermediate‐brackish marsh cover because gulf cordgrass and saltmeadow cordgrass dominate these marshes (Enwright et al ), and preliminary observations showed most black rail detections were in this marsh type. We used open water as a proxy for discontinuity in habitat at the site level.…”
Section: Methodsmentioning
confidence: 99%